2007
DOI: 10.1007/s00270-007-9121-7
|View full text |Cite
|
Sign up to set email alerts
|

Sexuality and Body Image After Uterine Artery Embolization and Hysterectomy in the Treatment of Uterine Fibroids: A Randomized Comparison

Abstract: In this paper the effect of uterine artery embolization (UAE) on sexual functioning and body image is investigated in a randomized comparison to hysterectomy for symptomatic uterine fibroids. The EMbolization versus hysterectoMY (EMMY) trial is a randomized controlled study, conducted at 28 Dutch hospitals. Patients were allocated hysterectomy (n = 89) or UAE (n = 88). Two validated questionnaires (the Sexual Activity Questionnaire [SAQ] and the Body Image Scale [BIS]) were completed by all patients at baselin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 36 publications
0
21
1
2
Order By: Relevance
“…With our search criterion, 107 individual records were found, but 13 publications [5][6][7][8][9][16][17][18][19][20][21][22][23] were Wnally included. Hehenkamp WJ et al study and other seven articles reported diVerent kinds of data in the same RCT, the randomized EMMY trial [6,[16][17][18][19][21][22][23].…”
Section: Meta-analysismentioning
confidence: 99%
“…With our search criterion, 107 individual records were found, but 13 publications [5][6][7][8][9][16][17][18][19][20][21][22][23] were Wnally included. Hehenkamp WJ et al study and other seven articles reported diVerent kinds of data in the same RCT, the randomized EMMY trial [6,[16][17][18][19][21][22][23].…”
Section: Meta-analysismentioning
confidence: 99%
“…In contrast to this case report, a study of 141 premenopausal women who underwent UAE for symptomatic fibroids observed significant improvements in sexual function and well being while problems associated with orgasm and pain reduced (Voogt et al 2008). Similar improvements in sexual activity and satisfaction following UAE have been described in other studies (Hehenkamp et al 2007;Smith et al 2004).…”
Section: Complications Of Fibroid Embolisationcontrasting
confidence: 69%
“…In both the groups sexual functioning and body image improved; however, significant increases were seen more often in the uterine artery embolization group. 51 Others conducted a large study comparing hysterectomy with endometrial ablation for dysfunctional uterine bleeding. This was a prospective cohort of over 11 000 women, of whom 8900 completed questions related to psychosexual function 5 years after treatment.…”
Section: Hysterectomy Versus Minimally Invasive Treatmentsmentioning
confidence: 99%